Ferromagnetic resonance studies of Co nanowire arrays - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
Co nanowires grown by electrodeposition technique on di-block copolymers composed of polystyrene and polymethylmethacrylate, P(S-B-MMA), have been studied. Two samples with the same wire length of I pm and different wire diameters of 12 and 24nm have been prepared. The nanowires are perpendicular to the film plane and arrayed in hexagonal symmetry in the lateral dimensions. Ferromagnetic resonance (FMR) technique has been used to investigate magnetic parameters of the system. The FMR spectra are very broad (a few kG) for every direction of the external field with respect to the sample plane. The FMR spectra exhibit considerable anisotropic behavior as the field is rotated both in sample plane and from the film plane towards the film normal direction. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: magnetic nanowires; nanostructures; ferromagnetic resonance; dipolar interaction; MAGNETIC NANOWIRES; NICKEL